Hubungan Kehamilan Remaja dengan Kejadian Stunting di Wilayah Kerja UPTD Puskesmas Tabukan - Aulia Rahmah; Hapisah; Megawati; Yuniarti (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Background: Stunting is a serious health issue affecting children's growth and development. Teenage pregnancy is a major risk factor that is often associated with the incidence of stunting. This study aims to determine the relationship between teenage pregnancy and the incidence of stunting in the working area of UPTD Puskesmas Tabukan. Methods: This study used an analytical observational design with a case-control approach, involving 192 children under five (96 stunted, 96 non-stunted). Data were collected from maternal and child health books, pregnancy registers, and EPPGBM records, and analyzed using the chi-square test.Results: Of the 96 children who experienced stunting, 44.8% of their mothers had been pregnant during adolescence. The chi-square test results showed a significant relationship between teenage pregnancy and stunting (p = 0.000) with an odds ratio of 4.5.Conclusion: Teenage pregnancy is associated with the incidence of stunting. Reproductive health education and improved access to health services for adolescents are needed to reduce the incidence of stunting. Latar Belakang: Stunting merupakan masalah kesehatan serius yang mempengaruhi pertumbuhan dan perkembangan anak. Kehamilan remaja merupakan faktor risiko utama yang sering berhubungan dengan kejadian stunting. Penelitian ini bertujuan untuk mengetahui hubungan antara kehamilan remaja dan kejadian stunting di wilayah kerja UPTD Puskesmas Tabukan. Metode: Penelitian ini menggunakan desain analitik observasional dengan pendekatan kasus kontrol, melibatkan 192 balita (96 stunting, 96 tidak stunting). Data dikumpulkan dari buku KIA, register kehamilan, dan catatan EPPGBM, serta dianalisis dengan uji chi-square. Hasil: Dari 96 balita yang mengalami stunting, 44,8% ibu mereka hamil pada usia remaja. Hasil uji chi-square menunjukkan hubungan signifikan antara kehamilan remaja dan stunting (p = 0,000) dengan rasio odds 4,5 kali. Kesimpulan: Kehamilan remaja berhubungan dengan kejadian stunting. Edukasi reproduksi dan peningkatan akses layanan kesehatan bagi remaja perlu dilakukan untuk menurunkan angka stunting. Kata Kunci: Stunting, Kehamilan Remaja, Balita, Puskesmas Tabukan